Voluptuous philosophy : literary materialism in the French Enlightenment - Meeker, Natania (Fordham University Press, 2006)
In 18th-century France, matter itself - in forms ranging from atoms to anatomies - became a privileged object of study. This book defines what is at stake in the emergence of an enlightened secular materialism by showing how questions of figure are consistently located at the very heart of 18th-century debates on the nature of material substance.